Postsynaptic cAMP signalling regulates the antagonistic balance of Drosophila glutamate receptor subtypes. - Zhao, K.; Hong, H.; Zhao, L.; Huang, S.; Gao, Y.; Metwally, E.; Jiang, Y.; Sigrist, S.J.; Zhang, Y.Q. (Development, 2020)
The balance among different subtypes of glutamate receptors (GluRs) is crucial for synaptic function and plasticity at excitatory synapses. However, the mechanisms balancing synaptic GluR subtypes remain unclear. Herein, we show that the two subtypes of GluRs (A and B) expressed at Drosophila neuromuscular junction synapses mutually antagonize each other in terms of their relative synaptic levels and affect subsynaptic localization of each other, as shown by super-resolution microscopy. Upon temperature shift-induced neuromuscular junction plasticity, GluR subtype A increased but subtype B decreased with a timecourse of hours. Inhibition of the activity of GluR subtype A led to imbalance of GluR subtypes towards more GluRIIA. To gain a better understanding of the signalling pathways underlying the balance of GluR subtypes, we performed an RNA interference screen of candidate genes and found that postsynaptic-specific knockdown of dunce, which encodes cAMP phosphodiesterase, increased levels of GluR subtype A but decreased subtype B. Furthermore, bidirectional alterations of postsynaptic cAMP signalling resulted in the same antagonistic regulation of the two GluR subtypes. Our findings thus identify a direct role of postsynaptic cAMP signalling in control of the plasticity-related balance of GluRs.